Mediation in the Medical Field: Is Neutral Intervention Possible? - Gibson, Kevin (The Hastings Center report, 1999)
Neutrality is held to be the touchstone of good mediation. True neutrality is elusive, however, and probably not even desirable, at least when applied to patient-provider disputes over medical care. In this context, mediators should not posture as “neutrals”; they should strive instead to protect their clients’ autonomy.